0% found this document useful (0 votes)
5 views

Simplifying Boolean Functions

Uploaded by

saimkhanhouse
Copyright
© © All Rights Reserved
Available Formats
Download as PPTX, PDF, TXT or read online on Scribd
0% found this document useful (0 votes)
5 views

Simplifying Boolean Functions

Uploaded by

saimkhanhouse
Copyright
© © All Rights Reserved
Available Formats
Download as PPTX, PDF, TXT or read online on Scribd
You are on page 1/ 9

Basic Rules of Boolean

Algebra
OR AND

x+xy = x(1+y)=x x(x+y)=xx+xy=x+xy=x(1+y)=x


mplementation of Boolean Functions
aw the logic diagram for the following functions
F = (a.b)+(b.c) a
b
F

F1 = x + y’z
x
F1

z
mplementation of Boolean Functions
Draw the logic diagram for:
F2  x' y ' z  x' yz  xy '

F2
z
mplementation of Boolean Functions
 Simplify F2 of previous example using Boolean rules
F2  x' y ' z  x' yz  xy '
x' z ( y ' y )  xy ' Distributive

x' z (1)  xy ' Complement

 x' z  xy '
x
y
F2

This implementation has fewer gates and fewer inputs to the gates (or wires) than
the previous one.
Simplifying Boolean Functions
Simplify following Boolean function to a min number of literals.

 F= x(+ y)
= xx+ xy = 0 + xy = xy Note:
Functions F and F1 are
the dual of each other,
 F1= x + (x’.y) hence output is also
= (x+x’)(x+y) = 1(x+y) = x+y dual.

 F2= (x + y) (x + y’)
= x+ xy +xy’ +yy’ = x(1+y+y’) = x (solving via expansion)

Solving F2 using Distributive law


F2= (x + y) (x + y’)
= (x + y)(x + y’) = x + yy’
Simplifying Boolean Functions
F3  xy  x' z  yz
 xy  x' z  yz ( x  x' ) Complement (x.x’)=1
xy  x' z  xyz  x' yz Distributed
xy  xyz  x' z  x' yz Rearrange order
 xy (1  z )  x' z (1  y ) Distributed
xy  x' z (X+1 =1)

F4= (x+y)(x’+z)(y+z)
By principle of duality F4 = xy + x’z + yz = F3 . Hence, ans = xy + x’z

x
y
F3

z
Complement of a Function
• The complement of a Function F is F’ is obtained by taking dual of the function
and then complementing each literal.

• Consider: A+B
• Dual: AB
• Complement: A'B’

• Consider F1=X’YZ’ +X’Y’Z


• Dual of F1 is = (X’+Y+Z’)(X’+Y’+Z) - Interchange AND and OR in func
• Complement each literal (X+Y’+Z)(X+Y+Z’) = F1’

 Complement follows DeMorgan’s Theorem which says


 (X+Y)’ = X’Y’ and (XY)’=X’+Y’
 Thus, in general (A+B+C+D+…+F)’= A’B’C’D’…. F’ and similarly
(ABCD…F)’ = A’+B’+C’+D’+… + F’
Complement of a Function
Take complement of F2 = [x(y’z’ + yz)]’
 Method 1: Using principle of duality

 Method 2: Using DeMorgan’s Theorem


More on complements (DeMorgan)
 Find the complement of following functions using DeMorgan’s Theorem:

F ( AB'C ) D' E F = x(x+y)


F ' [( AB'C ) D' E ]' F’=[ x( x  y )]'  x'( x  y )'
[( AB'C ) D ' ]' E ' x' x' y '
[( AB'C )' D' ' ]E '  x' (1  y ' )
[( AB' )' C ' D ]E '  x' (1)  x'
( A' B )C ' E ' DE '

You might also like